An alert radar: Anclajes in the critical agenda of contemporary literary studies (Anclajes, 2021)
Academic journals differ only in some criteria and formal aspects from cultural or literary journals. In both cases, they install or consolidate theoretical and critical lines. The anniversary of Anclajes offers an opportunity to review some of these lines in relation to literary studies on contemporaneity.
Keywords: academic journals; cultural magazines; literary criticism; XXI Century